Electroacupuncture Improves Cognitive Function in Senescence-Accelerated P8 (SAMP8) Mice via the NLRP3/Caspase-1 Pathway - Zhitao Hou; Ruijin Qiu; Qingshuang Wei; Yitian Liu; Meng Wang; Tingting Mei; Yue Zhang; Liying Song; Xianming Shao; Hongcai Shang; Jing Chen; Zhongren Sun (Neural Plasticity)
Background. Clinically, electroacupuncture (EA) is the most common therapy for aging-related cognitive impairment (CI). However, the underlying pathomechanism remains unidentified. The aims of this study were to observe the effect of EA on cognitive function and explore the potential mechanism by which EA acts on the NLRP3/caspase-1 signaling pathway. Main Methods. Thirty male SAMP8 mice were randomly divided into the model, the 2 Hz EA and 10 Hz EA groups. Ten male SAMR1 mice were assigned to the control group. Cognitive function was assessed through the Morris water maze test. Hippocampal morphology and cell death were observed by HE and TUNEL staining, respectively. The serum IL-1β, IL-6, IL-18, and TNF-α levels were measured by ELISA. Hippocampal NLRP3, ASC, caspase-1, GSDM-D, IL-1β, IL-18, Aβ, and tau proteins were detected by Western blotting. Key Findings. Cognitive function, hippocampal morphology, and TUNEL-positive cell counts were improved by both EA frequencies. The serum IL-1β, IL-6, IL-18, and TNF-α levels were decreased by EA treatment. However, 10 Hz EA reduced the number of TUNEL-positive cells in the CA1 region and serum IL-1β and IL-6 levels more effectively than 2 Hz EA. NLRP3/caspase-1 pathway-related proteins were significantly downregulated by EA, but 2 Hz EA did not effectively reduce ASC protein expression. Interestingly, both EA frequencies failed to reduce the expression of Aβ and tau proteins. Significance. The effects of 10 Hz EA at the GV20 and ST36 acupoints on the NLRP3/caspase-1 signaling pathway may be a mechanism by which this treatment relieves aging-related CI in mice.